A new era in cancer therapy: targeting the Proteasome-Bcl-2 axis - Sourabh Soni; Vandana Anang; Yutong Zhao; Jeffrey C. Horowitz; Richard S. Nho; Yohannes A. Mebratu (Journal of Experimental & Clinical Cancer Research)
Abstract The B-cell lymphoma-2 (Bcl-2) family proteins, key regulators of apoptosis, are frequently dysregulated in cancer, tipping the balance of cell survival and apoptosis in favor of survival. The ubiquitin-proteasome system (UPS) is a critical cellular machinery that controls the Bcl-2 levels through regulation of protein stability. This review delves into the intricate interplay between the proteasome and Bcl-2 family members, exploring how proteasome-mediated degradation impacts cell survival and proliferation to influence cancer progression. We discuss the therapeutic potential of targeting the proteasome-Bcl-2 axis, including the use of proteasome inhibitors as anticancer agents. We examine their mechanisms of action, clinical efficacy, and limitations while exploring emerging strategies to overcome these challenges.